Formação de terapeutas ocupacionais em consultoria colaborativa na escola: avaliação de um programa on line - Assis, Caroline Penteado de (2013)
The collaborative consultation in Occupational Therapy has been considered one of the most promising emerging practices in the field in education supported by international public policy. However achieving true practice of collaboration is still considered a challenge to be conquered, and in this context there is the need for continuing education of professionals working in the school area. Thus the aim of this research was to evaluate an on line collaborative consultation program in school for occupational therapists. Participants were seven occupational therapists and six teachers of students who are part of the target audience of Special Education. The Moodle platform was the virtual learning environment for the study. We used action research as a methodological design. We constructed several instruments to collect data specifically for the study, including: case studies, field diaries, reports on the practice; scripts for the focus groups, and program evaluation protocol. How standardized instrument was used only Canadian Occupational Performance Measure. The study was conducted in three stages, namely: development, implementation and evaluation. It was based program development in assumptions Deweyan pragmatism and collaborative learning. The program developed here titled "COLABORA" was composed of a theoretical part and a practical in which participants had to perform a concrete experience of collaborative consultation. Data were analyzed qualitatively from thematic categories. The results showed participants' performance (before, during and after the program), the repertoire of knowledge built by the participants and the process of learning online. It was found that the COLABORA produced important changes both in discourse and in practice performed by occupational therapists in the school context. It is noteworthy that in three collaborative partnerships was conducted to identify possible positive impact on student performance from the partnership of professionals with the teacher. In the process of online learning strategies were fundamental to collaborative learning results from the tools of collective discussion and case studies that promoted the association of theoretical practical concepts. The collaborative consultation favored the in-service training of school professionals promoting both the empowerment of professionals as the target enrollment of students in Special Education classes of regular schools.